The decline of fertility in Germany, 1871-1939 - Knodel, John E. (Princeton, New Jersey : Princeton University Press, 1974)
This is the second in a series of monographs on the historic decline of European fertility to be issued by the Office of Population Research at Princeton University. It is a detailed statistical description and analysis of the transition from high to low birth rates which took place in Germany between Unification and the beginning of World War II. It assembles an exceptionally comprehensive amount of evidence that will be of great importance to social historians as well as sociologists and demographers. John E. Knodel relies on modern yet simple methods of measuring the main demographic trends in Germany and uses straightforward methods to test the plausibility of the many hypotheses that have been advanced to explain the great falls in fertility that occurred throughout the western world in the late nineteenth century.Originally published in 1974.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
ConclusionEmigration, Inter-Provincial Migration, and Migration between Administrative Areas; Urbanization; Conclusion; Additional Social Variables.; Multivariate Analyses of the Fertility Decline.; Conclusion; Trends in Fertility and Nuptiality.; Social Differentials.; Infant Mortality.; Emigration and Migration.; The Social Context.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: Fertility, Human -- Germany -- History; Germany -- Population -- History; Fécondité humaine -- Allemagne -- Histoire; SOCIAL SCIENCE -- Sociology -- General; SOCIAL SCIENCE -- Anthropology -- General; SOCIAL SCIENCE -- Regional Studies; Fertility, Human; Population; Germany; History